Indic-nuristani sákth-i/án-, ćupti- and Albanian sup - Eric P. Hamp (Linguistica, 2002)
In Indogermanica et Caucasica: Festschrift für Karl Horst Schmidt zum 65. Geburtstag, edd. R. Bielmeier. and R. Stempel (Berlin: de Gruyter 1994) 38, I have reconstructed the laryngeal heteroclite *s VktH/n- 'thigh'. From the modem languages CDIAL adds more evidence. The basic noun is attested in Ashkun sot and Waigali sōt, whereby we recognize Nuristanī' s valuable contribution.